2014
DOI: 10.1016/j.neuroscience.2014.01.011
|View full text |Cite
|
Sign up to set email alerts
|

α4βδ-GABAARs in the hippocampal CA1 as a biomarker for resilience to activity-based anorexia

Abstract: Anorexia nervosa (AN) is a psychiatric illness characterized by restricted eating and an intense fear of gaining weight. Most individuals with AN are females, diagnosed first during adolescence, 40% to 80% of whom exhibit excessive exercise, and an equally high number with a history of anxiety disorder. We sought to determine the cellular basis for individual differences in AN vulnerability by using an animal model, activity-based anorexia (ABA), that is induced by combining food restriction (FR) with access t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 70 publications
6
35
0
Order By: Relevance
“…Spine membrane levels of extra-synaptic α4βδ-containing GABA A Rs, which mediate shunting inhibition at dendritic spines of stratum radiatum of the dorsal CA1 (Shen et al 2007), correlate strongly and negatively with the distances run by ABA animals (Aoki et al 2014). Importantly, these α4βδ-GABA A Rs are inactivated by allopregnanolone in a chloride ion-flux-dependent manner, a condition brought on in the dorsal CA1 of adolescent females when an animal is stressed (Shen et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Spine membrane levels of extra-synaptic α4βδ-containing GABA A Rs, which mediate shunting inhibition at dendritic spines of stratum radiatum of the dorsal CA1 (Shen et al 2007), correlate strongly and negatively with the distances run by ABA animals (Aoki et al 2014). Importantly, these α4βδ-GABA A Rs are inactivated by allopregnanolone in a chloride ion-flux-dependent manner, a condition brought on in the dorsal CA1 of adolescent females when an animal is stressed (Shen et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…ABA is induced readily in wild-type rodents by imposing food restriction in combination with access to a running wheel (Aoki et al 2014; Wable et al 2015b). This is an important behavior shared among individuals with AN (Davis et al 1997), with some studies indicating that all patients exhibit hyperactivity/over-exercise during the course of the illness and/or prior to diagnosis (Kron et al 1978).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there was, again, a strong correlation between the animal’s FR-evoked running and the level of α4βδ-GABA A Rs at spine membranes immediately adjacent to excitatory axo-spinous synapses (Fig. 2B in (Aoki et al, 2014b), with the most resilient animals having the most increased levels of α4βδ-GABA A R. When examined after only 2 days of FR, we, again, observed a strong correlation between α4βδ-GABA A R levels and the extent of the animal’s suppression of FR-evoked running. However, approximately half of the α4βδ-GABA A Rs resided in the spine cytoplasm, rather than at the plasma membrane (Fig.…”
Section: Activity-based Anorexia (Aba) An Animal Model Of Anorexiamentioning
confidence: 90%
“…Analysis of the hippocampus immediately at the end of the first ABA (after 4 days of FR) (Aoki et al, 2014b) revealed that some animals expressed levels of α4βδ-GABA A Rs that were nearly five-fold those of controls, while others exhibited levels no different from controls. Moreover, there was, again, a strong correlation between the animal’s FR-evoked running and the level of α4βδ-GABA A Rs at spine membranes immediately adjacent to excitatory axo-spinous synapses (Fig.…”
Section: Activity-based Anorexia (Aba) An Animal Model Of Anorexiamentioning
confidence: 99%